Present and future research for productive waqf management and administration in Malaysia - Mohamad, Nor Asiah; Syed Abdul Kader, Sharifah Zubaidah; Ali, Zuraidah (Serials Publication (P) Ltd, 2017)
This article discusses the latest trends in international waqf research for purposes of better management and administration in Malaysia. Its employs a doctrinal qualitative analysis, studying and analysing existing literature including research papers, statutes and primary authorities, in order to identify and recommends areas and the need for future research. The finding are that the trend and demand for waqf is no more restricted to identifying the basic legal framework and jurisprudence of waqf but the timely need to synergise, innovate, co-create and interface with other sectors and disciplines and strategising for waqf creation and development. In achieving the objective, the law must be strengthened, human capital management must be enhanced and support from the authorities is vital to match the professionalism of the complimentary sectors.